GAMBARAN LAMA PAJANAN DENGAN KADAR HbCO DALAM DARAH PADA PETUGAS RETRIBUSI TERMINAL PURABAYA BUNGURASIHSURABAYATAHUN 2015 - Agustin Wulansari; Rachmaniyah .; Imam Thohari (Poltekkes Kemenkes Surabaya, 2016)
Bus station activity, transportation operations creates high pollution of carbon monoxide (CO) which is so dangerous for retribution officers of Purabaya bus station, Bungurasih. HbCO level can be affected by long exposure. This research aims to describe exposure to carbon monoxide tested through HbCO in the blood of retribution officers of Purabaya Bus Station Bungurasih.This is a descriptive research with cross sectional approach and uses x Blood Gas analyzer method. Sample of the research was 12 retribution officersworkingin morning and afternoon shift. Data was analyzed by descriptive tabulation in the form of table.Interview was conducted to determine characteristics of the retribution officers of Purabaya Bus station, Bungurasih.Results showed that retribution officers possessed averageHbCO level of 11.94%, exposure duration per day of 8 hours was 66.7% and 41.7% officers had smoking habit of ½ - 2 packs/day.It is concluded that HbCO level in officers blood washigher than normal level( 5%). Improvement is needed in all aspects; all employees working outdoors are recommended to wear mass to filter gases or pollutants in which is harmful for health. They are recommended not to smoke when working. Manager of bus station also needsto do planting in bus station area.